Flower-like open-structured polycrystalline copper with synergistic multi-crystal plane for efficient electrocatalytic reduction of nitrate to ammonia. (15th June 2022) - Zhao, Yaling; Liu, Yang; Zhang, Zunjie; Mo, Zhenkun; Wang, Chenyi; Gao, Shuyan
Abstract: Electrocatalytic reduction of nitrate to ammonia is a promising way to regulate the global nitrogen cycle, and is also an important complementary means of ammonia synthesis. However, the convenient preparation of open-structured catalysts with synergistic multi-crystal plane to achieve high efficiency and selectivity is a great challenge. Herein, a flower-like open-structured polycrystalline copper loaded on carbon fiber papers is successfully prepared by linearly varying the deposition potential. This facile approach constructs an open reaction environment with heterogeneous synergistic polycrystalline copper surfaces during the 8-electron reaction, fully enhancing the liquid-phase mass transfer process and the synergistic catalysis process. The optimal sample exhibits the glorious nitrate reduction performance with high ammonia yield of 101.4 μmol h −1 cm −2 and Faradaic efficiency of 93.91% in neutral solution. This work develops a unique self-supporting heterogeneous interface for synergistic catalytic of nitrate, and offers new ideas for simple and rapid implementation of high-performance catalysts for ammonia production from nitrate. Graphical Abstract: ga1 This work develops a flower-like polycrystalline copper to provide the open reaction environment with heterogeneous synergistic multi-crystalline plane during the 8 - electron reaction, enhancing the liquid-phase mass transfer and synergistic catalysis process for ammonia production from nitrate. Highlights: This work develops a flower-like open-structured polycrystalline copper loaded on carbon paper. Open-structured heterogeneous interface achieves the effective exposure of Cu(100) and Cu(111). The optimal sample exhibits high NH3 yield (101.4 μmol h −1 cm −2 ) and Faradaic efficiency (93.91%). This work offers new ideas in synergistic catalytic of nitrate by unique polycrystalline interfaces.